Optimization of Tooth Color and Shade Guide Design - Rade D. Paravina, DDS, PhD;1 Goran Majkic, PhD;2 Francisco H. Imai, PhD;3 (Journal of Prosthodontics, 2007)
One critical prerequisite for dental shade guides is to match the color range and distribution of human teeth